Metamaterials in microwaves, optics, mechanics, thermodynamics, and transport. (21st July 2017) - Koschny, Thomas; Soukoulis, Costas M; Wegener, Martin
Abstract: We review the status of metamaterials on the occasion of the 15th birthday of the field with particular emphasis on our own contributions. Metamaterials in electromagnetism, mechanics, thermodynamics, and transport are covered. We emphasize that 3D printing, also known as additive manufacturing, inspires metamaterials—and vice versa.